Revised Multi-Chain PEGASIS for Wireless Sensor Networks - Sethi, Deepak; Pratim Bhattacharya, Partha (International Journal of Sensors Wireless Communications and Control, 2016)
In wireless sensor network, sensor nodes have limited power and processing capability. So, the main issue is to increase the network lifetime. The multichain concept in PEGASIS and sink mobility increases the network lifetime in wireless sensor network. In this research paper, we have proposed a revised multi-chain PEGASIS protocol by revising the position of the mobile sink to maximize the network lifetime. The simulation is done in MATLAB R2008a and results are compared with MIEEPB (Mobile sink improved energy- efficient PEGASIS-based routing protocol). Also, we have simulated revised multi-chain PEGASIS according to standard assumptions and results are satisfactory.
Keywords: Multi-chain PEGASIS